Analisis Pengaruh Diameter Sudu Pipa Elbow Terhadap Kinerja Turbin - Jamal Jamal; La Ode Musa; Joy E. Sitayani; Lovejuwantri Batu Pagallaran (Politeknik Negeri Ujung Pandang, 2023)
In this study, three turbines were tested with variations in the diameter of blades the elbow pipe, are ½ inch, ¾ inch and 1 inch, the three turbines were tested alternately. The working principle of the test installation is that the pump circulates pressurized water through a pipe from the lower reservoir to the nozzle, the water spray from the nozzle hits the turbine blades so that the turbine rotates, the water falls and flows back into the reservoir. The turbine rotation that occurs also causes the rotation of the pulley and generator. The rotating generator produces electricity, which is sent to the lamp load until it lights up. The lowest performance of the 90° elbow turbine is at an output power of 1.35 watt with a system efficiency of 28.28% occurring in the use of ½ inch diameter elbow blades while the highest is at 2.76 watt power with 62.10% efficiency occurring in the use of ¾ Inch diameter elbow blades. On average, turbine elbow ½ inch has an efficiency of 33.57%, turbine elbow ¾ inch has an efficiency of 43.65% and turbine elbow one inch has an efficiency of 46.46%.